Psychometric properties of the satisfaction with life scale (SWLS) in Iranian infertile women - Saman Maroufizadeh; Azadeh Ghaheri; Reza Omani Samani; Zahra Ezabadi (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2016)
Background: Infertility is a global public health issue and may adversely affect life satisfaction. One of the most widely instruments used to assess life satisfaction is the Satisfaction with Life Scale (SWLS). Objective: The objective of this study was to examine the psychometric properties of the SWLS in Iranian infertile women. Materials and Methods: In this descriptive cross-sectional study, a total of 125 infertile women referring to Royan Institute in Tehran were selected by convenience sampling method. The participants were administered the SWLS, the Hospital Anxiety and Depression Scale (HADS), and a demographic questionnaire. The psychometric properties of the SWLS were examined: construct validity using confirmatory factor analysis (CFA), reliability using Cronbach's alpha and convergent validity by examining the relationship with HADS. Result: Results of the CFA indicated that a single-factor model provides a good fit to the data (χ2/df= 1.58; GFI= 0.975; CFI= 0.995; NFI= 0.985; RMSEA= 0.069 and SRMR= 0.027). The Cronbach's alpha coefficient for SWLS was 0.887. Significant negative correlations were found between SWLS and HADS scores for anxiety (r= -0.410) and depression (r= -0.434), indicating an acceptable convergent validity. Conclusion: The SWLS has adequate psychometric properties for assessing life satisfaction in Iranian infertile women.